Is synchronised NIPPV more effective than NIPPV and NCPAP in treating apnoea of prematurity (AOP)? A randomised cross-over trial. Issue 1 (15th October 2014) - Gizzi, Camilla; Montecchia, Francesco; Panetta, Valentina; Castellano, Chiara; Mariani, Chiara; Campelli, Maristella; Papoff, Paola; Moretti, Corrado; Agostino, Rocco
Abstract : Background: Apnoea, desaturations and bradycardias are common problems in preterm infants which can be treated with nasal continuous positive airway pressure (NCPAP) and nasal intermittent positive pressure ventilation (NIPPV). It is unclear whether synchronised NIPPV (SNIPPV) would be even more effective. Objective: To assess the effects of flow-SNIPPV, NIPPV and NCPAP on the rate of desaturations and bradycardias in preterm infants and, secondarily, to evaluate their influence on pattern of breathing and gas exchange. Patients and methods: Nineteen infants (mean gestational age at study 30 weeks, 9 boys) with apnoeic spells were enrolled in a randomised controlled trial with a cross-over design. They received flow-SNIPPV, NIPPV and NCPAP for 4 h each. All modes were provided by a nasal conventional ventilator able to provide synchronisation by a pneumotachograph. The primary outcome was the event rate of desaturations (≤80% arterial oxygen saturation) and bradycardias (≤80 bpm) per hour, obtained from cardiorespiratory recordings. The incidence of central apnoeas (≥10 s) as well as baseline heart rate, FiO2, SpO2, transcutaneous blood gases and respiratory rate were also evaluated. Results: The median event rate per hour during flow-SNIPPV, NIPPV and NCPAP was 2.9, 6.1 and 5.9, respectively (p<0.001 and 0.009, compared with flow-SNIPPV). Central apnoeas per hour were 2.4, 6.3 and 5.4, respectively (p=0.001, for both compared with flow-SNIPPV), while no differences in any other parameter studied were recorded. Conclusions: Flow-SNIPPV seems more effective than NIPPV and NCPAP in reducing the incidence of desaturations, bradycardias and central apnoea episodes in preterm infants.